2013
DOI: 10.1115/1.4025583
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Analysis of a Multistage Axial Compressor Including Stall Prediction by Steady and Transient CFD Methods

Abstract: Siemens Energy has commissioned an extensive multiyear experimental and numerical (computational fluid dynamics (CFD)) project to improve its ability to design for and predict compressor stall. The experimental test rig is a half scale six stage axial compressor. The goal of this work is to provide insight into how best to predict the compressor performance map and in particular the stall point by applying state-of-the-art multiple blade row CFD simulation tools. A preliminary CFD analysis quantified numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The stall limit is detected by the numerical divergence of the solving process of steady calculations, and this approach for determining the stall limit of compressor has been adopted and demonstrated by many investigations, such as ref. 27,28 The minimum step of increasing the exit pressure before the stall condition achieves 5 Pa.
Figure 2.Mesh of NASA Stage 35.
…”
Section: Methodsmentioning
confidence: 99%
“…The stall limit is detected by the numerical divergence of the solving process of steady calculations, and this approach for determining the stall limit of compressor has been adopted and demonstrated by many investigations, such as ref. 27,28 The minimum step of increasing the exit pressure before the stall condition achieves 5 Pa.
Figure 2.Mesh of NASA Stage 35.
…”
Section: Methodsmentioning
confidence: 99%
“…It is important to state that the evaluation of multi-stage axial compressor working limits with CFD, using limited experimental data, is not straightforward. Simulations using a limited number of blade passages [22] with the RANS method often overestimate the compressor stability [23][24][25]. To estimate the critical flow characterisation responsible for operational limitations, advanced URANS or LES simulations are more appropriate to precisely determine the onset of stall [26,27].…”
Section: Power Augmentationmentioning
confidence: 99%
“…Commercial CFD ANSYS codes have been used to compare RANS/URANS transition and scale resolving simulation (SRS) turbulence methods. Studies showed that CFD simulation applications are computationally practicable and suitable for most of the turbo machinery design analysis [25][26][27]. Moreover, flow field simulations for predicting the action of turbine performance on freesurface flow situations have appeared due to the complex nature of this physic spectacle [10].…”
Section: Pre-processingmentioning
confidence: 99%